MASALAH PASANGAN SUAMI ISTRI YANG MENIKAH ANTAR ETNIS DALAM KELUARGA DAN MASYARAKAT DI KENAGARIAN AIA ANGEK KECAMATAN SIJUNJUNG KABUPATEN SIJUNJUNG - Sefputri, Eka; Kasih, Fitria; Nofrita, Nofrita (Bimbingan dan Konseling, 2014)
Communication error between couples who married between ethnic, and married couples who are not able to inter-ethnic adapt both within the family and in society. The study describes the problems faced by married couples seen from the aspect of inter-ethnic communication and aspects of adjustment in Kenagarian Aia Angek Sub district Sijunjung District Sinjunjung. This study used a descriptive analysis approach. The population includes individuals who were married between ethnic residing in Kenagarian Aia Angek Sub district Sijunjung District Sinjunjung that all research sample of 30 people. This research tool was a questionnaire. Analysis using the percentage formula. Results showed that married couples in inter-ethnic Kenagarian Aia Angek Sijunjung Sijunjung district including the District established a pretty good relationship. Neither of the way they communicate and of how adaptation to the family and society. This is evidenced from the results, the average alternative answers of respondents to the statements they give variable results obtained for communications at 48.42%, which means to do pretty well so its quite a problem occurs. So also of the way they conform to the average obtained alternative answers given by 47.4% of respondents are meant to do quite well, so it is quite a problem occurs.